Visual evoked Potential (VEP): Comparative study of physiological variation in children below 5 years and adults beyond 50 Years - Wadhera, Jyoti; Dudhmal, Vandana (International Journal of Medical Research and Review, 2015)
Introduction: Visual evoked Potential is the electrical potential difference recorded from the surface of scalp in response to Visual stimuli. It represents a resultant response of cortical as well as subcortical areas to photostimulation. Although various studies have been done on visual evoked potential but there are few studies from India only. Therefore this study was planned to compare visual evoked potentials by recording battery of N70, P100 & N155 waveform in children and adults beyond 50 years. Methods: Present study was conducted in department of Physiology of Tertiary care teaching hospital. 50 healthy patients were included in two groups, below 5 years and beyond 50 years. Visual evoked Potential has been recorded and their physiological Variation has been observed. Results: In our study on comparison between children and adults beyond 50 years there were no differences in amplitude and latency of N 70 and N155 waves observed. P100 latencies have shown statistically significant differences in amplitude and latencies although no differences in duration war observed. Conclusion: It is important that physiological variation should be kept in mind whenever we are making any interpretations. The change in P100 with age may reflect senile changes in eye and optic nerve especially beyond 60 years of age.